Novel Engraftment and T Cell Differentiation of Human Hematopoietic Cells in ART−/−IL2RG−/Y SCID Pigs - Boettcher, Adeline N.; Li, Yunsheng; Ahrens, Amanda P.; Kiupel, Matti; Byrne, Kristen A.; Loving, Crystal L.; Cino-Ozuna, A. Giselle; Wiarda, Jayne E.; Adur, Malavika; Schultz, Blythe; Swanson, Jack J.; Snella, Elizabeth M.; et al. (Frontiers in Immunology, 2020)
Pigs with severe combined immunodeficiency (SCID) are an emerging biomedical animal model. Swine are anatomically and physiologically more similar to humans than mice, making them an invaluable tool for preclinical regenerative medicine and cancer research. One essential step in further developing this model is the immunological humanization of SCID pigs. In this work we have generated T- B- NK- SCID pigs through site directed CRISPR/Cas9 mutagenesis of IL2RG within a naturally occurring DCLRE1C (Artemis)-/- genetic background. We confirmed Art-/- IL2RG-/Y pigs lacked T, B, and NK cells in both peripheral blood and lymphoid tissues. Additionally, we and successfully performed a bone marrow transplant on one Art-/- IL2RG-/Y male SCID pig with a bone marrow from a complete swine leukocyte antigen (SLA) matched donor without conditioning to reconstitute porcine T and NK cells. Next, we performed in utero injections of cultured human CD34+ selected cord blood cells into the fetal Art-/- IL2RG-/Y SCID pigs. At birth, human CD45+ CD3ε+ cells were detected in peripheral blood of in utero injected SCID piglets. Human leukocytes were also detected within the bone marrow, spleen, liver, thymus, and mesenteric lymph nodes of these animals. Taken together, we describe critical steps forwards the development of an immunologically humanized SCID pig model.